«DESIGNER EMBRYOS»: LEGAL AND BIOETHICAL ASPECTS - I. V. Ponkin; A. A. Ponkina (Акушерство, гинекология и репродукция, 2017)
The article describes the developing technologies for the production of «designer embryos» also known as genetically improved babies. The authors briefly review these technologies with a special emphasis on their medical, legal and bioethical aspects. We propose and substantiate the point of view why some of these approaches may be illegal.